Axon Guidance Molecules in the Islets of Langerhans - Waters, Bayley J.; Blum, Barak (Frontiers in Endocrinology, 2022)
The islets of Langerhans, responsible for regulating blood glucose in vertebrates, are clusters of endocrine cells distributed throughout the exocrine pancreas. The spatial architecture of the different cell types within the islets controls cell-cell communication and impacts their ability to collectively regulate glucose. Islets rely on a range of chemotactic and adhesive cues to establish and manage intercellular relationships. Growing evidence indicates that axon guidance molecules such as Slit-Robo, Semaphorin-Neuropilin, Ephrin-Eph, and Netrins, influence endocrine progenitors’ cell migration to establish correct architecture during islet morphogenesis, as well as directly regulating physical cell-cell communication in the mature islet to coordinate hormone secretion. In this review, we discuss what is known and not yet known about how axon guidance molecules contribute to islet morphogenesis and function.